Urban soil contamination with lead and cadmium in the playgrounds located near busy streets in Cracow (South Poland) - Aleksander-Kwaterczak, Urszula; Rajca, Aleksandra (Geology, Geophysics and Environment, 2015)
Pollution of urban soils with heavy metal caused by traffic activities is increasingly becoming a great threat to human health and environmental quality. This paper presents the results of research of lead (Pb) and cadmium (Cd) distribution in soils located on playgrounds situated near busy streets in Cracow (Poland). Samples of sand and soil were taken from the top layers (0-10 cm) of ground. Concentrations of examined metals are within the ranges: Pb from 6.80 to 54.04 mg/kg and Cd from 1.60 to 2.61 mg/kg. The highest concentrations were found in the points near the most traffic roads, but this phenomenon is much more visible in the case of lead than cadmium and for places where there is soil on the surface. For sand samples metals amounts are much lower. Although the results have not indicated a high degree of soil’s contamination, they point to the problem of the children's exposure to toxic metals. Urban soil should be monitored particularly in such special places as playgrounds.